Different Stages of Poultry Production Require Specific Nutrient Profiles - Aldahmani, Haifa; Saqaa Rasah, Marwah (AlQalam Journal of Medical and Applied Sciences, 2026)
There is an urgent need for optimized nutritional control based on the prevailing physiology of different production phases for optimizing poultry performance. In this background, the purpose of the study: the purpose of the study is to investigate how the different nutrient requirements of the different stages can impact growth, feed conversion, reproduction, and health. In this research, efforts were made to provide poultry with highly optimized nutritional diets as required by different stages of poultry production, which included starter, grower, finisher, and layer stages. For instance, in this study, some of the parameters under observation included growth rate, feed consumption rate, feed conversion rate, reproduction performances, egg quality, and health conditions. The findings of this research revealed that feeding poultry as per stages can greatly improve their growing performances, especially in the starter and finisher stages, and can also properly meet their reproduction requirements during the layers stage. Additionally, feeding poultry with minerals during the reproductive stages can improve eggshell quality and maintain poultry health, whereas there were low mortality percentages in all stages. These findings clearly indicate that feeding poultry using uniform practices just because of their equal protein and energy requirements is not effective for meeting their optimized requirements throughout their life span. A balanced diet for poultry production will always take into account stage-wise optimization to ensure effective use of poultry feeds and to enhance production, along with environmental and economic sustainability.